Physician burnout in Nigeria: a multicentre, cross-sectional study - Arinze D. G. Nwosu; Edmund N. Ossai; Uwakwe C. Mba; Ifeanyi Anikwe; Richard Ewah; Bernard O. Obande; Justin U. Achor (BMC, 2020)
Abstract Background Healthcare workers are a burnout-prone occupational group and the prevalence is particularly high among physicians. With the prevailing low physician-patient ratio in Nigeria which has worsened with the recent wave of physician emigration, among other socio-economic constraints; a setting for high physician burnout may have been nurtured. Our survey set out to determine the prevalence of burnout among physicians practicing in Nigeria, ascertain the factors that were associated with the development of burnout and evaluate the respondents' perceived impact of physician burnout on patient safety. Methods We used the Oldenburg burnout inventory as the measurement tool for burnout in the cross-sectional study conducted between November and December, 2019 among physicians in five tertiary health institutions in Nigeria. A 5- point Likert-type scale was used to evaluate the participants rating of their perceived impact of physician burnout on patient safety. Data entry and analysis were done using IBM Statistical package for social sciences software version 25 and the level of statistical significance was determined by a p value < 0.05. Results The response rate was 61% (535/871), and burnout prevalence was 75.5% (404/535). Majority of the physicians (74.6%) perceive that physician burnout could impact patient safety. Physicians' professional grade, age and years in practice, but not specialty, gender or marital status were associated with the exhaustion domain, whereas only the physicians' age was associated with the disengagement domain of burnout. No socio-demographic or work-related characteristics determined overall burnout in our respondents. Conclusion Physician burnout in Nigeria is high and pervasive, and this should alert physicians to be wary of their general and mental health status. Public health policy should address this development which has implications for patient safety, physician safety and healthcare system performance.